Conceptual Design and Hydrodynamic Performance of a Modular Hybrid Floating Foundation - Xiaobin Qu; Yingxue Yao; Jianjun Du (Energies, 2021)
The comprehensive utilization of offshore renewable energies is an effective way to solve the intermittency and variability of power supply. This paper aims to present a hybrid floating system (HFS) based on a modular buoyancy-distributed floating foundation (BDFF) that can be equipped with a horizontal-axis wind turbine, solar panels, and wave energy converters (WEC). A simplified test model with a Froude scale ratio of 1/10 is employed to perform the experiments in a deep-water basin to validate the numerical results computed from the code program ANSYS AQWA based on the potential flow theory. The Response Amplitude Operators (RAOs) under regular waves are compared to evaluate the hydrodynamic performance. There is a good agreement in the surge, pitch, and heave RAOs for experiments and the numerical simulation, with a maximum of 6.45 degrees per meter for the pitch motion. Furthermore, the mooring tensions in the time domain are analyzed under different wave conditions.The tension RAOs from simulations are slightly higher than those from measurements with a maximum value at the period of 3.416 s. The mooring line on the windward side has a more considerable mooring tension that is far less than the allowable tensile strength, especially under the wave height of 2 m and the wave period of 2.873 s. The influence of loaded weight representing solar panels is weak, and the impact of winds is acceptable, as the platform deviates 1.3 degrees from the equilibrium state under the test wind speed. Eventually, the effect of irregular waves on the HFS is presented with the critical parameters of mooring tension and pitch motion. The results show that the HFS has a good motion performance.